Mild–Moderate TBI: Clinical Recommendations to Optimize Neurobehavioral Functioning, Learning, and Adaptation - Chen, Anthony J.-W.; Loya, Fred (Seminars in Neurology, 2014)
Traumatic brain injury (TBI) can result in functional deficits that persist long after acute injury. The authors present a case study of an individual who experienced some of the most common debilitating problems that characterize the chronic phase of mild-to-moderate TBI—difficulties with neurobehavioral functions that manifest via complaints of distractibility, poor memory, disorganization, poor frustration tolerance, and feeling easily overwhelmed. They present a rational strategy for management that addresses important domain-general targets likely to have far-ranging benefits. This integrated, longitudinal, and multifaceted approach first addresses approachable targets and provides an important foundation to enhance the success of other, more specific interventions requiring specialty intervention. The overall approach places an emphasis on accomplishing two major categories of clinical objectives: optimizing current functioning and enhancing learning and adaptation to support improvement of functioning in the long-term for individuals living with brain injury.
Keywords: brain injury; chronic deficits; cognition; emotion; attention; memory; fatigue; rehabilitation